Early maladaptive schemas in child sexual exploitation material users: implications for their intrapersonal and interpersonal problems - Turhan, Huseyin Mert (2024)
Child sexual exploitation material (CSEM) users are a type of child sex offenders that have a specific interest in using, collecting and/or trading child sexual abuse materials. CSEM users suffer from persistent and maladaptive cognitions that support their CSEM use; and are indicative of their compulsive sexual behaviours (CSB), problems in emotional regulation, as well as influences from adverse parental behaviours (e.g., abuse, neglect). Current conceptualisations of intrapersonal and interpersonal problems of CSEM users solely focus on their CSEM use and often disregard the fundamental cognitive mechanisms behind CSEM use. Early maladaptive schemas (EMS) reflect maladaptive cognitions and beliefs that represent individuals’ perceptions of the world surrounding them; these schemas constitute problematic patterns of cognitions, behaviours and emotions that shape individuals’ intrapersonal and interpersonal problems. However, there is a lack of research in the literature concerning the influence of EMS on the intrapersonal and interpersonal problems experienced by CSEM users. EMS can be utilised to understand the fundamental cognitive mechanisms behind CSEM use and inform about how CSEM users’ fundamental perceptions of themselves and others potentially influence their intrapersonal and interpersonal problems.